Discovery of Robust Ferroelectricity in 2D Defective Semiconductor α‑Ga2Se3. Issue 8 (8th December 2021) - Xue, Wuhong; Jiang, Qitao; Wang, Fakun; He, Ri; Pang, Ruixue; Yang, Huali; Wang, Peng; Yang, Ruilong; Zhong, Zhicheng; Zhai, Tianyou; Xu, Xiaohong
Abstract: 2D ferroelectrics with robust polar order in the atomic‐scale thickness at room temperature are needed to miniaturize ferroelectric devices and tackle challenges imposed by traditional ferroelectrics. These materials usually have polar point group structure regarding as a prerequisite of ferroelectricity. Yet, to introduce polar structure into otherwise nonpolar 2D materials for producing ferroelectricity remains a challenge. Here, by combining first‐principles calculations and experimental studies, it is reported that the native Ga vacancy‐defects located in the asymmetrical sites in cubic defective semiconductor α‑Ga2 Se3 can induce polar structure. Meanwhile, the induced polarization can be switched in a moderate energy barrier. The switched polarization is observed in 2D α‑Ga2 Se3 nanoflakes of ≈4 nm with a high switching temperature up to 450 K. Such polarization switching could arise from the displacement of Ga vacancy between neighboring asymmetrical sites by applying an electric field. This work removes the point group limit for ferroelectricity, expanding the range of 2D ferroelectrics into the native defective semiconductors. Abstract : A new ferroelectric phase is observed in 2D defective semiconductor α‑Ga2 Se3 by introducing Ga vacancies into asymmetrical sites and their movement at neighboring sites. Switched polarization can occur in nanoflakes of ≈4 nm with a high switching temperature of 450 K. This work provides a 2D ferroelectric system‐defective semiconductor that enables more functionality and more flexible modulation.